Long-term adaptation to dietary shifts of gut microbiota in gilthead seabream (Sparus aurata) - Ruiz, Alberto; Alós, Josep; Gisbert, Enric; Furones, Dolors; Viver, Tomeu (Frontiers in Marine Science, 2024)
In many meta-analyses and literature reviews on fish microbiota, the provenance of the animals (farmed vs. wild) is often overlooked. Given the well-established role of diet as a key factor in shaping gut microbiota, this study investigates the impact of dietary nature by comparing the microbiota of gilthead seabream (Sparus aurata) fed a commercial diet versus a wild-type diet, all reared within a recirculating aquaculture system. Over a 60-day period, we tracked changes in gut bacterial diversity, structure, and composition following a shift from a commercial feed to a diet exclusively based on pink shrimp (Parapenaeus longirostris). Gut bacterial communities were assessed using 16S rRNA gene sequencing (Illumina MiSeq platform) with primers targeting the V3-V4 hypervariable regions. Twenty days after the dietary change, microbial diversity (Shannon index) increased in fish fed the shrimp diet compared to those fed the commercial diet, while Dominance index values decreased. Additionally, inter-individual (beta-) diversity based on Bray-Curtis distances also differed between dietary treatments. These results support further that microbiota comparisons between farmed/captive and wild fish are challenging due to the unpredictable feeding regimes and dietary variations in wild fish. However, the diet impact on microbiota diminished over time, with the differences in intra- and inter-individual diversity being reduced after 40 days, which suggests an adaptation of microbial communities to dietary changes. At this point, gut microbial communities also showed a similar taxonomical composition. Moreover, a core microbiota consisting of species belonging to the genera Ralstonia, Paraburkholderia, Fulvimonas, Pseudomonas, and Cutibacterium was maintained in all sampling times under both dietary treatments. Overall, this study serves as a conceptual approach that shows a long-term adaptation of the gut microbiota after a radical dietary change, probably driven by host-inherent factors. Furthermore, these results may be a valuable insight for feed manufacturers aiming to develop sustainable and cost-effective ingredients since they suggest that some alternative feeds and ingredients do not have adverse long-term effects on fish gut microbiota.